UPAYA INDONESIA DALAM REPATRIASI WARGA EKS TIMOR TIMUR (2000 – 2012) - Yogi Mulia; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The conflict between Indonesia, pro - Integration fighters of Indonesia, and the East Timor freedom fighters is the cause of more than 280,000 people of East Timor did a great exodus to the Indonesian territory. Refugees in Indonesian territory has a positive effect and a bad effect on the lives of local people. Therefore, the Indonesian government made a policy to implement the option to become Indonesian citizens or choose to do Repatriation.For the theory used in this research is the theory of decision making, while the concept used is the concept of National Interest (National-interest). In carrying out the policy, Indonesian government has made several repatriation programs both independently and with assisted.To solve these problems the Indonesian government made various efforts including resettlement, transmigrastion to other areas in Indonesia, and repatriation program. In the repatriation program, in addition to making domestic policy called BAKORNAS – PBP Indonesian government is also working with international organizations such as UNHCR, IOM and CIS Timor.Key words: Decision Making, Policy, Repatriation, Refugees, Cooperation.